Chromohysteroscopy after failed intracytoplasmic sperm injection - Khalifa, Emad E.; El Samra, Mohamed A.; Said, Tamer H.; Abdin, Noha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: ICSI is the injection of a single sperm directly into the cytoplasm of the oocyte (ICSI). The failure to achieve pregnancy after ICSI has been studied over many years to reach the possible and preventable causes to avoid another failure. The aim of this study was to assess the value of using Chromohysteroscopy as a part of the work up of cases with one or more failed ICSI. The Ultimate goal is to detect the possible endometrial abnormalities and /or endometritis. Methods: Prospective cohort study was carried out with total of 50 infertile women recruited from infertility clinic in Elshatby Maternity University Hospital, Alexandria University, Egypt. Cases were allocated in 2 groups with 25 cases in each group. The first group included cases that had a failed trial of ICSI. The second group included control cases who were seeking for fertility treatment with no previous history of ICSI or any uterine surgery or anatomical abnormalities. In the postmenstrual period, Chromohysteroscopy was done by the same surgeon and documentation of all findings in the cavity and presence of endometritis. Results: There was a significant increase in the incidence of endometritis among the study group 68% in comparison to 16% in the control group. Conclusions: In this study endometrial dying with methylene blue at hysteroscopy improve the detection of chronic endometritis.